Опозиційна діяльність : поняття, основні риси, перспективи - Котова, Л. В.; Kotova, L. (My University, 2010)
The article deals with common description of opposition activity, its concept, functions and perspectives. Refer to scientists who developed this problem. Describe an experience of political opposition existence in Western countries.
Котова Л. В. Опозиційна діяльність : поняття, основні риси, перспективи / Л. В. Котова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 259-265.
Keywords: опозиційна діяльність; політична опозиційна діяльність; опозиционная деятельность; политическая опозиционная деятельность; vocally oppose activities; vocally oppose the political activities